The Virginia Slims identity crisis: an inside look at tobacco industry marketing to women. Issue 3 (27th May 2005) - Toll, B A; Ling, P M
Abstract : Objectives: Because no prior studies have comprehensively analysed previously secret tobacco industry documents describing marketing female brands, the Virginia Slims brand was studied to explore how Philip Morris and competitors develop and adapt promotional campaigns targeting women. Methods: Analysis of previously secret tobacco industry documents. The majority of the documents used were from Philip Morris. Results: The key to Virginia Slims advertising was creating an aspirational image which women associated with the brand. Virginia Slims co-opted women's liberation slogans to build a modern female image from 1968 through to the 1980s, and its market share grew from 0.24% to 3.16% during that time period. Ironically, the feminist image that worked very well for the brand was also the reason for its subsequent problems. Philip Morris experienced unprecedented losses in market share in the early 1990s, with a decline in market share for four consecutive years from 3.16% to 2.26%; they attributed this decline to both the fact that the brand's feminist image no longer appealed to young women aged 18–24 years, and increased competition from more contemporary and lower priced competitors. Throughout the 1990s, attempts to reacquire young women while retaining Virginia Slims loyal (now older) smokers were made using a "King Size" line extension, new slogans, and loyalty building promotions. Conclusions: Tobacco advertisers initially created distinct female brands with aspirational images; continued appeal to young women was critical for long term growth. The need for established brands to evolve to maintain relevance to young women creates an opportunity for tobacco counter-marketing, which should undermine tobacco brand imagery and promote aspirational smoke-free lifestyle images. Young women age 18–24 are extremely valuable to the tobacco industry and should be a focus for tobacco control programmes.